Preparation process of hematite-containing polyethylene flame-retardant mute material for pipes
By using polyethylene flame retardant silent material preparation process containing hematite in drain pipe materials, combined with modified nanocarbon black, expandable graphite and ammonium polyphosphate, a dense carbon layer is formed to improve flame retardant performance and through coupling The agent coats hematite particles, solving the problems of high material manufacturing cost and poor flame retardant effect in the prior art, and achieving better silent and environmental stress resistance.
Patent Information
- Application Number
- CN202411597366.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing drainage pipe materials have high manufacturing cost and poor flame retardant effect, and the material has high brittleness and poor environmental stress cracking resistance.
The preparation process of polyethylene flame retardant silent material containing hematite is adopted. By pretreatment of hematite and combining modified nanocarbon black, modified expandable graphite and ammonium polyphosphate as flame retardants, a dense carbon layer is formed to Improve flame retardant properties and coat hematite particles with coupling agent to reduce processing wear and improve silence.
It significantly improves the flame retardant performance and silent effect of the material, while reducing production costs, ensuring the strength and environmental stress resistance of the material.
Smart Images

Figure CN119144074A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drainage pipe materials, and in particular to a preparation process of a hematite-containing polyethylene flame-retardant and sound-silencing material for pipes. Background Art
[0002] A Chinese patent with publication number CN114573897A discloses a special material for polyethylene silent drain pipes and a preparation method thereof, which relates to the technical field of drain pipe preparation, and solves the technical problems of large brittleness and unsatisfactory environmental stress cracking resistance of existing drain pipes. The material comprises the following components: active barium sulfate powder, EBS, polyethylene wax, calcium stearate, antioxidant, maleic anhydride grafted polyethylene, linear low-density polyethylene, and high-density polyethylene; chemical chains are formed in the inventive system to improve the adhesion and coupling between maleic anhydride grafted polyethylene and the above materials; in addition, EBS enables the active barium sulfate powder to be more fully dispersed in maleic anhydride grafted polyethylene, linear low-density polyethylene, and high-density polyethylene, thereby increasing the rate of branching stress and diffusion stress of the material; the active barium sulfate powder has a hydrophobic and lipophilic structure, which makes its interface bonding with linear low-density polyethylene and high-density polyethylene more uniform and firmer; the material has excellent strength, hardness and modulus, and environmental stress cracking resistance. However, in the above-mentioned prior art solutions, barium sulfate is selected as the weight-increasing material to increase the surface density of the pipe, but it is expensive, which increases the manufacturing cost; and the prepared material has poor flame retardant effect; therefore, the present invention provides a preparation process of a polyethylene flame retardant and sound-proof material containing hematite for pipes to solve the above-mentioned problems. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a process for preparing a polyethylene flame retardant and soundproofing material containing hematite for pipes, which solves the problems mentioned in the above background technology.
[0004] To achieve the above objectives, the present invention is implemented through the following technical scheme: A preparation process of polyethylene flame retardant and soundproof material containing hematite for pipes, comprising the following preparation steps: Step 1: Grind 60-80 g of hematite, pass it through a 600-1250 mesh sieve, and perform pretreatment; Step 2: Add the pretreated hematite, 5-8g of flame retardant, 0.2-1g of external lubricant, 0.3-1g of internal lubricant, and 25-35g of high-density polyethylene into an internal mixer, heat and mix to 190-195°C, then pour into the feeding hopper of a single screw extruder, and extrude and granulate through a single screw extruder at an extruder temperature of 140-170°C; In the step 1, the hematite powder is pretreated with a titanate coupling agent or an aluminate coupling agent, and the mass ratio of the coupling agent to the hematite powder is 10: (0.1-0.4); The external lubricant is selected from one of calcium stearate and zinc stearate, and the internal lubricant is white oil; The flame retardant is a composition of modified nano carbon black, modified expandable graphite and ammonium polyphosphate, and the weight percentage of each component added is: 30wt% to 42wt% of modified nano carbon black, 30wt% to 38wt% of modified expandable graphite and 25wt% to 36wt% of ammonium polyphosphate.
[0005] Preferably, the preparation method of the modified nano carbon black is: S1. hydroxylating the surface of 1.5-2 g of nano carbon black; S2, then epoxidizing the surface; S3, pour into 100 mL of anhydrous ethanol and disperse by ultrasonic for 50 to 60 minutes; S4, pour 25-28 g of EP-POSS into 50-70 mL of anhydrous ethanol, and after it is completely dissolved, slowly add it dropwise to the solution of S3, and stir the reaction at 55-60 ° C for 10-12 h; S5, pour 2.5-3.2 g of sodium aminobenzenesulfonate into a mixed solution of 22-28 mL of deionized water and anhydrous ethanol to dissolve, then slowly add dropwise to the reaction solution of S4, and continue the reaction for 10-12 hours; S6. After the reaction is completed, the mixture is filtered, washed with deionized water and anhydrous ethanol in turn, filtered, dried in a drying oven at 95-100° C., and then ground to obtain modified nano carbon black.
[0006] Preferably, in S5, the mass ratio of deionized water to anhydrous ethanol is 1:1.
[0007] Preferably, the specific processing steps of hydroxylation in S1 are: S11, pour 1.5-2g of nano carbon black into 100-180mL of hydrogen peroxide solution, stir and mix for 5-7min, and then disperse by ultrasonic for 30-35min; S12, heating to 55-60°C and stirring for 22-24h; S13, after the reaction is completed, filter and rinse with deionized water; S14. Place in an oven at 75-80°C and dry for 10-12 hours.
[0008] Preferably, the specific processing steps of epoxidation in S2 are: S21, mixing ethanol and deionized water to prepare a 100 mL mixed solution; S22, add 0.8-1.5 g of KH550 and perform ultrasonic treatment for 10-15 min; S23, adding 0.5-0.8 g of nano carbon black with hydroxylation treatment on the surface, and ultrasonically dispersing for 1.8-2 h; S24, heating to 75-78°C, stirring and reflux for 5-6h; S25. After the reaction is completed, the mixture is filtered and washed by centrifugation with anhydrous ethanol for 4 to 5 times, and then dried in a vacuum drying oven at 55 to 60° C. for 10 to 12 hours.
[0009] Preferably, in S21, the volume ratio of ethanol to deionized water is 9:1.
[0010] Preferably, the preparation and modification method of the modified expandable graphite is: add 180-200g of anhydrous ethanol to 2-5g of KH570, mix well, heat the mixture to 75-80°C in a water bath, then pour in 100-110g of dried expandable graphite, stir for 25-30min at a stirring speed of 1300-1500rmp, and obtain the modified expandable graphite.
[0011] Preferably, the preparation method of the dried expandable graphite is: placing the expandable graphite in a drying oven at 80-85° C. and drying it for 3-4 hours.
[0012] The present invention provides a preparation process of a polyethylene flame retardant and soundproof material containing hematite for pipes. Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation process of the polyethylene flame retardant and soundproofing material containing hematite for the pipe is as follows: by pre-treating the ground hematite so that its exterior is coated with a coupling agent, the wear of the hematite on the processing equipment is greatly reduced, the bonding ability between the hematite particles and the matrix is enhanced, the soundproofing effect of the material is significantly improved, and the production cost is reduced.
[0013] (2) The preparation process of the polyethylene flame retardant and soundproofing material containing hematite for the pipe comprises the following steps: modifying nano carbon black so that it can play a synergistic flame retardant role with sulfonate in the condensed phase. The two can promote the formation of a dense carbon layer in the matrix, which has a good barrier effect; modifying expandable graphite so that it forms a condensed phase on the polymer surface, isolating the air, preventing heat transfer, and reducing the release of combustible gases, thereby achieving the purpose of flame retardancy; adding ammonium polyphosphate, the viscous ammonium polyphosphate and expandable graphite at high temperature form a continuous and dense carbon layer, isolating the contact between air and the material surface, and the carbon black is evenly dispersed in the carbon layer, so that the formed carbon layer has better thermal insulation performance, thereby hindering the transfer of heat and contact with oxygen during the combustion process, and reducing the volatilization of combustible gases. Through their synergistic effect, the flame retardant performance of the material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1This is a density test comparison chart provided by the present invention. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0016] A preparation process of a polyethylene flame retardant and soundproof material containing hematite for pipes, comprising the following preparation steps: Step 1: Grind 60 g of hematite and pass it through a 600-mesh sieve, and pretreat the hematite powder with a titanate coupling agent or an aluminate coupling agent, and the mass ratio of the coupling agent to the hematite powder is 10:0.1; Step 2: Add the pretreated hematite, 8 g of flame retardant, 1 g of calcium stearate, 0.3 g of white oil, and 35 g of high-density polyethylene into an internal mixer, heat and mix to 190° C., then pour into the feed hopper of a single-screw extruder, and extrude and granulate through a single-screw extruder at a temperature of 140° C.; Wherein, the flame retardant is a composition of 30wt% modified nano carbon black, 38wt% modified expandable graphite and 32wt% ammonium polyphosphate; The preparation method of modified nano carbon black is: S1. Pour 1.5 g of nano carbon black into 100 mL of hydrogen peroxide solution, stir and mix for 5 min, and then ultrasonically disperse for 30 min; heat to 55 ° C and stir to react for 22 h; after the reaction is completed, filter and rinse with deionized water; place in an oven at 75 ° C to dry for 10 h; S2, mix ethanol and deionized water in a volume ratio of 9:1 to prepare a 100 mL mixed solution; add 0.8 g of KH550, and ultrasonically treat for 10 min; then add 0.5 g of the treated nano carbon black in S1, and ultrasonically disperse for 1.8 h; heat to 75°C, stir and reflux for 5 h; after the reaction is completed, filter, wash with anhydrous ethanol by centrifugation 4 times, and then dry in a vacuum drying oven at 55°C for 10 h; S3, pour into 100 mL of anhydrous ethanol and disperse by ultrasonic for 50 min; S4, pour 25g of EP-POSS into 50mL of anhydrous ethanol, and after it is completely dissolved, slowly add it dropwise to the solution of S3, and stir the reaction at 55°C for 10h; S5, pour 2.5g of sodium aminobenzenesulfonate into 22mL of a mixed solution of deionized water and anhydrous ethanol in a mass ratio of 1:1, dissolve it, then slowly add it dropwise to the reaction solution of S4, and continue the reaction for 10h; after the reaction is completed, filter it with suction, wash it with deionized water and anhydrous ethanol in turn, filter it, dry it in a drying oven at 95°C, and then grind it to obtain modified nano carbon black; The preparation and modification method of the modified expandable graphite is as follows: placing the expandable graphite in a drying oven at 80°C for 3 hours; adding 180g of anhydrous ethanol to 2g of KH570, mixing, heating the mixture to 75°C in a water bath, and then pouring in 100g of dried expandable graphite, stirring for 25 minutes at a stirring speed of 13000rmp, to obtain the modified expandable graphite. Example 2
[0017] A preparation process of a polyethylene flame retardant and soundproof material containing hematite for pipes, comprising the following preparation steps: Step 1: Grind 70 g of hematite and pass it through an 800-mesh sieve, and pretreat the hematite powder with a titanate coupling agent or an aluminate coupling agent, and the mass ratio of the coupling agent to the hematite powder is 10:0.2; Step 2: Add the pretreated hematite, 6.5 g of flame retardant, 0.6 g of zinc stearate, 0.6 g of white oil, and 30 g of high-density polyethylene into an internal mixer, heat and mix to 195° C., then pour into the feeding hopper of a single-screw extruder, and extrude and granulate through a single-screw extruder at a temperature of 150° C.; Wherein, the flame retardant is a composition of 36wt% modified nano carbon black, 34wt% modified expandable graphite and 30wt% ammonium polyphosphate; The preparation method of modified nano carbon black is: S1. Pour 1.8 g of nano carbon black into 140 mL of hydrogen peroxide solution, stir and mix for 6 min, and then ultrasonically disperse for 32 min; heat to 60 ° C and stir to react for 23 h; after the reaction is completed, filter and rinse with deionized water; place in an oven at 75 ° C to dry for 11 h; S2, mix ethanol and deionized water in a volume ratio of 9:1 to prepare a 100 mL mixed solution; add 1.2 g of KH550, and ultrasonically treat for 12 min; then add 0.7 g of the treated nano carbon black in S1, and ultrasonically disperse for 1.9 h; heat to 76 ° C, stir and reflux for 5 h; after the reaction is completed, filter, wash with anhydrous ethanol by centrifugation for 5 times, and then dry in a vacuum drying oven at 55 ° C for 11 h; S3, pour into 100 mL of anhydrous ethanol and disperse by ultrasound for 55 min; S4, pour 26g of EP-POSS into 60mL of anhydrous ethanol, and after it is completely dissolved, slowly add it dropwise to the solution of S3, and stir the reaction at 60°C for 11h; S5, pour 2.8g of sodium aminobenzenesulfonate into 25mL of a mixed solution of deionized water and anhydrous ethanol in a mass ratio of 1:1, dissolve it, and then slowly add it dropwise to the reaction solution of S4, and continue the reaction for 11h; after the reaction is completed, filter it with suction, and wash it with deionized water and anhydrous ethanol in turn, filter it, and then dry it in a drying oven at 98°C and grind it to obtain modified nano carbon black; The preparation and modification method of the modified expandable graphite is as follows: placing the expandable graphite in a drying oven at 85°C for 3h; adding 190g of anhydrous ethanol to 3g of KH570, mixing, heating the water bath to 75°C, and then pouring 105g of dried expandable graphite, stirring for 30min at a stirring speed of 1400rmp to obtain the modified expandable graphite. Example 3
[0018] A preparation process of a polyethylene flame retardant and soundproof material containing hematite for pipes, comprising the following preparation steps: Step 1: Grind 80 g of hematite and pass it through a 1250 mesh sieve, and pretreat the hematite powder with a titanate coupling agent or an aluminate coupling agent, and the mass ratio of the coupling agent to the hematite powder is 10:0.4; Step 2: Add the pretreated hematite, 5 g of flame retardant, 0.2 g of calcium stearate, 0.3 g of white oil, and 25 g of high-density polyethylene into an internal mixer, heat and mix to 195° C., then pour into the feed hopper of a single-screw extruder, and extrude and granulate through a single-screw extruder at a temperature of 170° C.; Wherein, the flame retardant is a composition of 42wt% modified nano carbon black, 30wt% modified expandable graphite and 28wt% ammonium polyphosphate; The preparation method of modified nano carbon black is: S1. Pour 2g of nano carbon black into 180mL of hydrogen peroxide solution, stir and mix for 7min, and then ultrasonically disperse for 35min; heat to 60°C and stir to react for 24h; after the reaction is completed, filter and rinse with deionized water; dry in an oven at 80°C for 12h; S2, mix ethanol and deionized water in a volume ratio of 9:1 to prepare a 100 mL mixed solution; add 1.5 g of KH550, and ultrasonically treat for 15 min; then add 0.8 g of the treated nano carbon black in S1, and ultrasonically disperse for 2 h; heat to 78 ° C, stir and reflux for 6 h; after the reaction is completed, filter, wash with anhydrous ethanol by centrifugation for 5 times, and then dry in a vacuum drying oven at 60 ° C for 12 h; S3, pour into 100 mL of anhydrous ethanol and disperse by ultrasonic for 60 min; S4, pour 28g of EP-POSS into 70mL of anhydrous ethanol, and after it is completely dissolved, slowly add it dropwise to the solution of S3, and stir the reaction at 60°C for 12h; S5, pour 3.2g of sodium aminobenzenesulfonate into 28mL of a mixed solution of deionized water and anhydrous ethanol in a mass ratio of 1:1, dissolve it, then slowly add it dropwise to the reaction solution of S4, and continue the reaction for 12h; after the reaction is completed, filter it with suction, wash it with deionized water and anhydrous ethanol in turn, filter it, dry it in a drying oven at 100°C, and then grind it to obtain modified nano carbon black; The preparation and modification method of the modified expandable graphite is as follows: placing the expandable graphite in a drying oven at 85°C for 4 hours; adding 200g of anhydrous ethanol to 5g of KH570, mixing, heating the water bath to 80°C, and then pouring 110g of dried expandable graphite, stirring for 30 minutes at a stirring speed of 1500rmp to obtain the modified expandable graphite.
[0019] Comparative Example 1 Compared with Example 1, the hematite in Example 1 is replaced by barium sulfate powder, and no pretreatment is required.
[0020] Comparative Example 2 Compared with Example 1, the flame retardant in Example 1 is replaced by a composition of modified carbon black and modified expandable graphite.
[0021] Comparative Example 3 Compared with Example 1, the flame retardant in Example 1 is replaced by a composition of nano carbon black, expandable graphite and ammonium polyphosphate.
[0022] Density test: Use JJ500 electronic analytical balance to test the density of standard strips molded by injection molding machine. The test standard is GB / T 9341-2000, and the sample size is 10mm×4mm×80mm.
[0023] Limiting oxygen index (LOI): The test was conducted using a JF-3 oxygen index tester in accordance with GB / T 2406-93. The sample size was 120 mm × 6.5 mm × 3.2 mm. The results are shown in Table 1.
[0024] Vertical combustion performance: CZF-3 horizontal vertical combustion tester was used to test according to the standard method of ASTMD-635-77. The sample size was 125mm×13mm×3.2mm. The results are shown in Table 1.
[0025] Tensile strength test: The test was conducted in accordance with GB / T 1040.1-2006, with a sample size of 120 mm × 10 mm × 4 mm; the results are shown in Table 1.
[0026] Table 1
[0027] As shown in Table 1, the flame retardant properties of the material prepared by the present technical solution are significantly improved while ensuring that its own mechanical properties are not affected.
[0028] According to the sound insulation principle of silent materials and the industry standards of relevant countries, the density of the material can achieve the effect of sound insulation and silence when it reaches a certain level. The "Industry Standards of Urban Construction of the People's Republic of China" stipulates that the density of sound-reducing materials is higher than 1800kg / m 3 , it can achieve the purpose of sound insulation and silence.
[0029] like Figure 1 As shown, the density of the materials prepared in Examples 1-3 is significantly greater than the density of the materials prepared in Comparative Examples 1-3. Therefore, the sound-absorbing effect of the materials prepared in Examples 1-3 is significantly improved.
[0030] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation process of polyethylene flame retardant and soundproof material containing hematite for pipes, It is characterized in that The method comprises the following preparation steps: Step 1: Grind 60-80 g of hematite, pass it through a 600-1250 mesh sieve, and perform pretreatment; Step 2: Add the pretreated hematite, 5-8g of flame retardant, 0.2-1g of external lubricant, 0.3-1g of internal lubricant, and 25-35g of high-density polyethylene into an internal mixer, heat and mix to 190-195°C, then pour into the feeding hopper of a single screw extruder, and extrude and granulate through a single screw extruder at an extruder temperature of 140-170°C; In the step 1, the hematite powder is pretreated with a titanate coupling agent or an aluminate coupling agent, and the mass ratio of the coupling agent to the hematite powder is 10: (0.1-0.4); The external lubricant is selected from one of calcium stearate and zinc stearate, and the internal lubricant is white oil; The flame retardant is a composition of modified nano carbon black, modified expandable graphite and ammonium polyphosphate, and the weight percentage of each component added is: 30wt% to 42wt% of modified nano carbon black, 30wt% to 38wt% of modified expandable graphite and 25wt% to 36wt% of ammonium polyphosphate.
2. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 1, Features: The preparation method of the modified nano carbon black is: S1. hydroxylating the surface of 1.5-2 g of nano carbon black; S2, then epoxidizing the surface; S3, pour into 100 mL of anhydrous ethanol and disperse by ultrasonic for 50 to 60 minutes; S4, pour 25-28 g of EP-POSS into 50-70 mL of anhydrous ethanol, and after it is completely dissolved, slowly add it dropwise to the solution of S3, and stir the reaction at 55-60 ° C for 10-12 h; S5, pour 2.5-3.2 g of sodium aminobenzenesulfonate into a mixed solution of 22-28 mL of deionized water and anhydrous ethanol to dissolve, then slowly add it dropwise to the reaction solution of S4, and continue the reaction for 10-12 hours; S6. After the reaction is completed, the mixture is filtered, washed with deionized water and anhydrous ethanol in turn, filtered, dried in a drying oven at 95-100° C., and then ground to obtain modified nano carbon black.
3. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 2, Features In S5, the mass ratio of deionized water to anhydrous ethanol is 1:
1.
4. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 2, Features: The specific processing steps of hydroxylation in S1 are: S11, pour 1.5-2g of nano carbon black into 100-180mL of hydrogen peroxide solution, stir and mix for 5-7min, and then disperse by ultrasonic for 30-35min; S12, heating to 55-60°C and stirring for 22-24h; S13, after the reaction is completed, filter and rinse with deionized water; S14. Place in an oven at 75-80°C and dry for 10-12 hours.
5. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 4, Features: The specific processing steps of epoxidation in S2 are: S21, mixing ethanol and deionized water to prepare a 100 mL mixed solution; S22, add 0.8-1.5 g of KH550 and perform ultrasonic treatment for 10-15 min; S23, adding 0.5-0.8 g of nano carbon black with hydroxylation treatment on the surface, and ultrasonically dispersing for 1.8-2 h; S24, heating to 75-78°C, stirring and reflux for 5-6h; S25. After the reaction is completed, the mixture is filtered and washed by centrifugation with anhydrous ethanol for 4 to 5 times, and then dried in a vacuum drying oven at 55 to 60° C. for 10 to 12 hours.
6. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 5, Features: In the S21, the volume ratio of ethanol to deionized water is 9:
1.
7. The preparation process of the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 1, Features: The preparation and modification method of the modified expandable graphite is as follows: 180-200g of anhydrous ethanol is added to 2-5g of KH570, mixed, heated to 75-80°C in a water bath, and then 100-110g of dry expandable graphite is poured in, stirred for 25-30min at a stirring speed of 1300-1500rmp, to obtain the modified expandable graphite.
8. The process for preparing the polyethylene flame retardant and soundproof material containing hematite for pipes according to claim 7, Features: The method for preparing the dried expandable graphite is as follows: placing the expandable graphite in a drying oven at 80-85° C. and drying it for 3-4 hours.
Citation Information
Patent Citations
High weather-resistant spray-free metal-imitating ABS composite material
CN107163493A
Composite wood material
CN107379137A
Special material for polyethylene mute drain pipe and preparation method thereof
CN114573897A
